HOMOGENITAS TARGET DALAM MATRIK PADA ANALISIS RESIDU PESTISIDA KARBAMAT DALAM TOMAT - Retno Yusiasih (Research Center for Chemistry - LIPI, 2009)
Optimum condition of carbamate are carbofurane and carbaryl recidues pesticide analysis by height performance liquid crhomatography (HPLC) has been done. The optimum condition are isocratic mobile please on acetonitrile/H20 :45/55 (v/v) and wave lenght of ultra violet (UV) detector has optimum absorbance at 275 nm. Performance of HPLC verification has minimum detection are 60 pbb for carbofurane and 40 ppb for carbaryl. Linierity and work range are 0.06 to 0.15 ppb for carbofurane with r2 value of 0.9702 and 0.04 to 0.15 ppb for carbaryl with r2 value of 0.09874. Precision of HPLC was showed by relative standard deviation (RSD), for carbofurane are 0.30 % of retention time (Rt) and 7.2 % of area. Whereas for carbaryl, the RSD are 0.20 % for Rt and 4.63 % for area. Homogeneity of targets in tomato matric as well as carbaofurane and carbaryl are homogen by analysis of varians (ONOVA) method which. is showed by F-value < F-critis. Homogeneity anlysis by National Acreditation of Comeetee (KAN) method also homogen with criteria I. Keywords: Homogeneity, Pesticide, Carbamate, Carbofurane,Carbaryl, Chromatographs.